Overskilling, Job Insecurity and Career Mobility - Wooden, M; McGuiness, S (My University, 2007)
This paper uses longitudinal data from Australia to examine the extent to which overskilling – the extent to which work-related skills and abilities are utilized in current employment – is a transitory phenomenon. The results suggest that while overskilled workers are much more likely to want to quit their current job, they are also relatively unconfident of finding an improved job match. Furthermore, some of the greater mobility observed among overskilled workers is due to involuntary job separations, and even in instances where job separations are voluntary, the majority of moves do not result in improved skills matches.
IZA Discussion Papers
Keywords: Employment; Education and Training; Employment -- Security of employment; Education and Training -- Overskilling; Employment -- Labour mobility; Learning, education and training; Labour market; Education and Training; Employment; Security of employment; Labour mobility; Overskilling; Employment and unemployment; Learning, education and training